1997
DOI: 10.1002/aic.690430627
|View full text |Cite
|
Sign up to set email alerts
|

Flow pattern transition maps for microgravity two‐phase flows

Abstract: Two-phase gas-liquid (and vapor-liquid) flows occur in a variety of process equipment such as petroleum production facilities, condensers and reboilers, power systems and core cooling of nuclear power plants during emergency operation. In addition to these normal gravity applications, two-phase flows also occur in many space operations such as active thermal control systems, power cycles, propulsion devices, and storage and transfer of cryogenic fluids.For conditions of technological interest, there are a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 6 publications
3
34
1
Order By: Relevance
“…It may be indicated that the two-phase¯ows are still developing due to the short length-to-diameter ratio of the test tube used in the present study. For the cases of middle and high gas¯ow rate, however, the predictions of Lee's model are very close to that of the drift-¯ux model with the value of transitional quality determined by Jayawardena et al (1997) and that of the semi-theoretical Weber number model, respectively. It is indicated that such¯ows might be close to fully developed and the entrance e ect may be neglected.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…It may be indicated that the two-phase¯ows are still developing due to the short length-to-diameter ratio of the test tube used in the present study. For the cases of middle and high gas¯ow rate, however, the predictions of Lee's model are very close to that of the drift-¯ux model with the value of transitional quality determined by Jayawardena et al (1997) and that of the semi-theoretical Weber number model, respectively. It is indicated that such¯ows might be close to fully developed and the entrance e ect may be neglected.…”
Section: Resultssupporting
confidence: 54%
“…An alternative relationship can be obtained by rearranging the empirical bubble-to-slug transition criterion proposed by Jayawardena et al (1997), which reads as…”
Section: Bubble-to-intermittent Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two empirical correlations for the transitional quality, which were proposed by Colin et al (1996) and Jayawardena et al (1997) based on the same database of two-phase flows in normal size channel at microgravity conditions. Detailed comment on them can be found in .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed comment on them can be found in . Here, for the later citation, only the correlation of Jayawardena et al (1997) is given as following,…”
Section: Discussionmentioning
confidence: 99%